2010
DOI: 10.1007/s11916-010-0146-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Tension-type Headache

Abstract: Tension-type headache (TTH) is the most prevalent type of headache across all age groups worldwide. TTH is common, disabling, and associated with medical and psychiatric comorbidities. This review will focus on the epidemiologies of episodic and chronic TTH in various age groups, factors associated with progression and remission, comorbidities, and the burden of TTH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 49 publications
1
64
0
3
Order By: Relevance
“…Headaches are common in all age groups. 12,28,56 Since pineal cysts are also common, a substantial number of patients will present for medical attention with headaches and a pineal cyst that is coincidentally rather than causally associated. In a surgical series of 11 patients with pineal cysts, Fetell et al 19 found that patients with headaches can be expected to have postoperative symptomatic relief only if the headaches were caused by hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…Headaches are common in all age groups. 12,28,56 Since pineal cysts are also common, a substantial number of patients will present for medical attention with headaches and a pineal cyst that is coincidentally rather than causally associated. In a surgical series of 11 patients with pineal cysts, Fetell et al 19 found that patients with headaches can be expected to have postoperative symptomatic relief only if the headaches were caused by hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…In a face-to-face study in which the entire population of a city in Brazil was investigated, oneyear prevalence of headache was 65.4% 3 , and distribution of headache types were in alignment with other studies from Brazil 4,5 . Headaches are a frequent cause of consultation in the specialty care 6,2 .…”
mentioning
confidence: 99%
“…While the biological mechanisms that predict progression from episodic TTH to chronic TTH have yet to be clarified, the epidemiologic literature has identified both depression and anxiety, and medication overuse, as primary factors that increase the risk of headache progression [1]. Taken together, the research discussed above suggests that more precise classification of TTH may require a more refined analysis of known precipitants and determinants.…”
Section: Journal Of Headache and Pain Managementmentioning
confidence: 99%
“…Tension-type headache (TTH) is the most prevalent form of headache in all age groups across the globe [1][2][3]. TTH leads to considerable disability [4, 5] with up to 60% of individuals reporting decreased work effectiveness [6], increased absenteeism [7], and reduced social engagement [6].…”
Section: Introductionmentioning
confidence: 99%